Bark water affects the isotopic composition of xylem water in tropical rainforest trees - Adriana Vega Grau; John Herbohn; Susanne Schmidt; Jeffrey McDonnell; Jeffrey McDonnell; Jeffrey McDonnell (Frontiers in Forests and Global Change)
The movement of water between xylem and inner bark (phloem and associated tissues), mostly driven by water potential differences, forms a key part of the diel transpiration cycle. It is not known how the use of water stored in bark at the diel transpiration cycle may influence the isotopic composition of xylem water. Understanding these possible effects is a major challenge for the identification of tree water sources and the interpretation of water use patterns using isotopes. Here, we examined the variation in the isotopic composition of water in inner bark and xylem at the diel scale and assessed how this varied in relation to traits and water use strategies on nine tree species in a tropical rainforest at the end of the dry season. We measured δ2H and δ18O in bark and xylem at two shallow depths: ‘outer xylem’ and ‘inner xylem’ (up to ~0.5 cm and ~ 1 cm from inner bark, respectively) collected at predawn, morning and midday. Considering all species together, the average isotopic composition of water in bark and outer xylem was similar at predawn and midday, suggesting water exchange between these tissues was reflected at these times, but differed significantly in the morning during increased transpiration. Results suggest that bark-xylem water exchange throughout the diel transpiration cycle affects the isotopic composition of xylem water in tropical rainforest trees. Furthermore, variations in δ2H and δ18O between xylem and bark were more pronounced in a deep-rooted, more isohydric species with dense wood than in a shallow-rooted, more anisohydric species with low wood density. This may suggest differences related to traits and hydraulic strategies in the reliance of bark-stored water across the diel cycle to buffer changes in xylem water potential. We discuss implications for interpreting tropical tree water sources in relation to water use strategies.